1989
DOI: 10.1063/1.102342
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal silicide precipitation in silicon induced by rapid thermal processing and free-surface gettering

Abstract: We have investigated the effect of nickel and copper on defect formation in silicon employing the rapid thermal processing (RTP) scheme. Treatment by RTP induces haze in the silicon wafer front side when its back side is contaminated by either nickel or copper. Transmission electron microscopy studies showed that the haze consisted of metal silicide precipitates, which negates a previous suggestion that ‘‘oxidation-induced stacking faults’’ are the main defect forming the haze. The morphology and nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The only other growth shape which could explain these observations would be a pyramid with four {111} faces and a square basal {001} face. This shape can be excluded, as it is not consistent with the symmetry of the cubic crystal system and can only be achieved for NiSi 2 precipitates when the basal {001} face is supported by Si surface orientation 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only other growth shape which could explain these observations would be a pyramid with four {111} faces and a square basal {001} face. This shape can be excluded, as it is not consistent with the symmetry of the cubic crystal system and can only be achieved for NiSi 2 precipitates when the basal {001} face is supported by Si surface orientation 12.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. 9–14 for an overview). NiSi 2 has fluorite structure, with Ni atoms placed on corners and face centres of the unit cell, while all tetrahedral interstitial sites are occupied by Si atoms (space group Fm$\overline {3} $ m 15, a (NiSi 2 ) = 5.408 Å 16).…”
Section: Introductionmentioning
confidence: 99%
“…Other TEM studies [94,95] provide an alternative possibility to enhance Cu precipitate stability. These works identified the formation of CuSi rather than Cu 3 Si for Cu precipitation in silicon and at the silicon surface.…”
Section: Study Of the Thermal Stability Of Copper Precipitates In Silmentioning
confidence: 99%
“…8 For the same reason, nickel can easily form a precipitate in silicon during the subsequent process, which can detrimentally affect the active device area. [9][10][11][12][13][14][15] Various aspects of nickel precipitates and their accompanying secondary defects in silicon have been reported, 11 and it was revealed that NiSi 2 , which has the calcium fluoride (CaF 2 ) structure, is the most preferred phase in crystalline silicon because it has the lowest lattice mismatch with the silicon matrix. [16][17][18] In addition, various extended defects such as stacking faults and dislocations in CZ-Si have been investigated under various experimental conditions.…”
mentioning
confidence: 99%
“…[16][17][18] In addition, various extended defects such as stacking faults and dislocations in CZ-Si have been investigated under various experimental conditions. 17 However, most of these studies considered wafer samples that are contaminated from the surface and in-diffused at a certain temperature [10][11][12][13][14][15][16][17][18][19][20] or doped during float-zone (FZ) growth. 21,22 These experimental conditions are a good approximation for the surface contamination of nickel, but they cannot reflect the exact behavior of nickel that appears during the CZ-Si growth process, which is accompanied with other impurities such as dopants and the formation of secondary defects during the subsequent wafering process.…”
mentioning
confidence: 99%